2015
DOI: 10.1111/bjso.12130
|View full text |Cite
|
Sign up to set email alerts
|

High construal level can help negotiators to reach integrative agreements: The role of information exchange and judgement accuracy

Abstract: In negotiations, a focus on interests (why negotiators want something) is key to integrative agreements. Yet, many negotiators spontaneously focus on positions (what they want), with suboptimal outcomes. Our research applies construal-level theory to negotiations and proposes that a high construal level instigates a focus on interests during negotiations which, in turn, positively affects outcomes. In particular, we tested the notion that the effect of construal level on outcomes was mediated by information ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…A core assumption of the theory is that the closer an “object” is – that is, an event, person, group, goal, or in the present case, an imagined state of society – the more concretely we mentally construe it; the further away it is, whether temporally, spatially, socially, or psychologically, the more abstractly we tend to construe it (Trope & Liberman, ). Abstract representations of distant objects constitute high‐level construals, and they are essential to planning, understanding, and integrating others' perspectives into one's own, as well as considering alternative possibilities and hypothetical outcomes (Trope & Liberman, ; Wening, Keith, & Abele, ).…”
Section: A Social Psychological Framework For Studying the Effects Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…A core assumption of the theory is that the closer an “object” is – that is, an event, person, group, goal, or in the present case, an imagined state of society – the more concretely we mentally construe it; the further away it is, whether temporally, spatially, socially, or psychologically, the more abstractly we tend to construe it (Trope & Liberman, ). Abstract representations of distant objects constitute high‐level construals, and they are essential to planning, understanding, and integrating others' perspectives into one's own, as well as considering alternative possibilities and hypothetical outcomes (Trope & Liberman, ; Wening, Keith, & Abele, ).…”
Section: A Social Psychological Framework For Studying the Effects Ofmentioning
confidence: 99%
“…High-level construal also promotes self-control (Carnevale et al, 2015;Fujita & Carnevale, 2012;MacGregor et al, 2017), a more realistic assessment of one's abilities (Yan, Hou, & Unger, 2014), and a stronger sense that one's goals are meaningful and self-concordant (Davis et al, 2016). In the context of bargaining and negotiation, which may be relevant to the implementation of social change, adopting an abstract (vs. concrete) mindset tends to increase information sharing and the likelihood of obtaining an integrative (win-win) solution (Wening et al, 2016). In a separate line of research, political conservatives who were prompted to think in more abstract terms subsequently expressed more concerns about fairness as well as less prejudice and more outgroup tolerance with respect to stigmatized, non-normative groups such as gay men, lesbians, Muslims, and atheists (Napier & Dovidio, 2012).…”
Section: The Cognitive-motivational Routementioning
confidence: 99%
“…The current research examines whether construal level might be a factor that differentially leads to adding or unbundling. Previous negotiation research demonstrated that construal level can foster forming integrative agreements using well-defined negotiation situations (e.g., Giacomantonio, De Dreu, & Mannetti, 2010;Henderson & Trope, 2009;Henderson, Trope, & Carnevale, 2006;Wening, Keith, & Abele, 2015). The current research extends this work on construal level to explore its effects on negotiations that allow parties to redefine the issues under consideration.…”
Section: Motivation and Contribution Of The Dissertation Researchmentioning
confidence: 65%
“…Construal level influences individuals' information processing (Förster, Epstude, & Özelsel, 2009;Forster, Ozelsel, & Epstude, 2010), knowledge representation (Liberman, Sagristano, & Trope, 2002), prediction (Henderson, Fujita, Trope, & Liberman, 2006;Nussbaum, Liberman, & Trope, 2006), decision making (Goodman & Malkoc, 2012;Pronin, Olivola, & Kennedy, 2008), and negotiation (Giacomantonio, De Dreu, Shalvi, Sligte, & Leder, 2010;Wening et al, 2015). For example, Henderson, Trope, and Carnevale (2006) found that adopting high-level construals led negotiators to consider multiple issues at the same time, which in turn led to forming tradeoffs.…”
Section: Construal Level Theorymentioning
confidence: 99%
“…Procrastination in people with a belief in entity intelligence tend to avoid the fear of failure, which can be buffered by the effect of high-level construal. High mental construal instigates a focus on interests during negotiations, which could positively affect outcomes (Wening, Keith, & Abele, 2015). Especially students that tend to believe in the entity theory and avoid doing their tasks might find it necessary to imagine a long-term plan and develop an interest in essential meaning, rather than imagine a short-term plan.…”
Section: Discussionmentioning
confidence: 99%